Dampak Penerapan Kurikulum Kementerian Agama dan Kurikulum Pesantren terhadap Peningkatan Hasil Belajar Pendidikan Agama Islam di Madrasah Aliyah Negeri Yogyakarta I - Ainna Khoiron Nawali (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2018)
Abstract: This research background is originated from increasing number of madrasah and general school curriculum as a curriculum support, especially on the subject of islamic religious education (PAI). It makes some institutions maintain either lodge, hostel, or boarding school, in order to encourage school programs. For instance, MAN Yogyakarta 1 established boarding school ‘Al Hakim’ to increase horizon of students towards scientific references to Islam. The question is, how do implementation of Kemenag curriculum and boarding school curriculm impact to elevate learning outcomes of PAI. This study attempts to determine for applicating two curriculum derived from kemenag and boarding school. This study utilizes qualitative research. The results show that in practice, kemenag curriculum remains a priority rather than boarding school curriculum; impact and achievement in the implementation of two curriculum have positive impact on learning outcomes such as to have better values on cognitive, affective, and psychomotor; excess two curricula are applied properly will create more students mastering the subject matter of religion. However, drawbacks occur discrepancy between the curriculum from kemenag and boarding school because the materials are not delivered properly and allocated short time. Keywords: Curriculum, Learning Outcomes, Islamic Religious Education